China?s Study On The Lift System In Deep Ocean Mining - Z. Weisheng (The Southern African Institute of Mining and Metallurgy, 2007)
The lift system is the main part in manganese nodule mining on the ocean bed. It connects the nodule collection system (miner) with the surface platform (mining vessel) and transports the nodules from the ocean bed to the surface. China started the research on lift technology in deep ocean mining in 1991, and a slurry pump hydraulic lift method has been developed for the nodule mining system. The detailed slurry pump hydraulic lift experiments have been undertaken with crushed nodules in the vertical pipe. The lift parameters to lift coarse particles in the lift pipeline have been discussed, including the pressure drop, the solid concentration, and the mixture velocity. The author of this paper not only took part in all these studies on the lifting technology, but was also responsible for some of this research. This paper will present the component parts of the lift system and the research results of coarse particle mixture flow in the vertical lift pipeline. Keywords: deep sea mining, slurry pump lift, lifting parameters.